Is our recommendation for smoking cessation considered in patients with Graves disease and Graves orbitopathy? (Annals of Medical Research, 2023)
Aim: Smoking increases the risk of Graves' orbitopathy (GO) in patients with Graves' disease (GD). Therefore, smoking cessation should be recommended to all patients with GD. This study aimed to investigate whether smoking cessation recommendations were taken into account in patients with GD and whether there was a difference in terms of smoking cessation between those with and without GO.Materials and Methods: Smoking status of the cases followed up with GD, who were active smokers when diagnosed, were questioned by telephone visit. The relationship of these data with the presence of GO was evaluated.Results: 74 smokers with GD were included in the study. All patients were advised to quit smoking by their physicians. While the number of cigarettes was 20 (10-22)/day at the first visit, the current cigarette use was 7 (0-15)/day, (p